Evaluation of a gravity-driven automated nasal irrigation system compared with manual syringe irrigation: a randomized crossover trial - Wacharaprapapong, Pichanon; Kulalert, Prapasri; Punyashthira, Patcharaporn; Poachanukoon, Orapan; Sritipsukho, Paskorn; Nanthapisal, Sira (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Large-volume saline nasal irrigation is widely recommended for sinonasal hygiene, but device design and pressure control influence effectiveness and tolerability. A novel automated irrigation device (NasiCare) utilizes gravity-regulated flow to deliver consistent low-pressure irrigation and may improve user experience compared with manual syringe use. Objectives were to compare the effects of an automated nasal irrigation device versus manual syringe irrigation on mucociliary clearance (MCC), safety, and user satisfaction in healthy adults. Methods: In this prospective, single-blind, randomized crossover trial, 40 healthy volunteers aged 18-60 years completed two intervention visits: automated NasiCare irrigation and manual syringe irrigation. MCC was assessed using saccharin transit time (STT) pre- and post-irrigation. Adverse effects were recorded using a standardized checklist, and user satisfaction was evaluated across four domains (0-10 visual analog scale). Results: Baseline pre-irrigation STT did not differ significantly between devices (median 6.58 vs. 6.95 minutes; p=0.380). Both devices resulted in significant post-irrigation STT improvement (p<0.001 for each), with no difference in post-irrigation STT (median 4.76 vs. 4.91 minutes; p=1.000) or STT change (1.59 vs. 1.53 minutes; p=0.085). Adverse events were infrequent and similar between groups, although nasal pain or tightness occurred only with syringe irrigation. Satisfaction scores were significantly higher for NasiCare across all domains, including overall satisfaction (median 10.0 vs. 7.0; p<0.001). Conclusions: Automated low-pressure nasal irrigation provides MCC benefits comparable to manual syringe irrigation while demonstrating superior user acceptability and similar safety. These findings support the automated device as a reliable and more user-friendly alternative for routine nasal irrigation.